Kurikulum Pendidikan Islam Moderat dalam Perspektif al-Qur’an - Hasan Maksum; Ahmad Fathinul Albab (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
Education in Indonesia faces major challenges related to the practice of violence and radicalization that still flourish in the educational environment, both at the elementary school to university level. This creates difficulties in designing a curriculum that reflects the principles of tolerance and diversity. This study aims to analyze the role of Islamic education in overcoming these problems through the application of the principle of religious moderation. Based on the literature review, it is found that religious moderation, as taught in the Qur'an, includes the principles of justice, friendship between religious communities, and the prohibition of imposing religion on others. The implementation of the principle of religious moderation in the Islamic Religious Education (PAI) curriculum can be done by including moderation content in each material, learning approaches that promote critical thinking and tolerance, and involving special training programs. Despite challenges such as student disinterest in religious studies and the influence of global culture, with the right strategies, Islamic education can play a role in creating a peaceful and inclusive educational environment. Therefore, religious moderation should be an integral part of the curriculum to shape a more tolerant and civilized generation.